Lenvatinib versus bevacizumab when combined with PD-1/L1 inhibitor and hepatic arterial infusion chemotherapy in unresectable hepatocellular carcinoma - Lichang Huang; Yujie Xu; Na Liu; Hailong Chen; Zichao Wu; Qijiong Li; Minqiang Lu; Wei Wei; Yaojun Zhang; Minshan Chen; Li Xu; Ming Shi; et al. (Frontiers in Immunology)
IntroductionThe combination of anti-angiogenic agents, PD-1/L1 inhibitors, and hepatic arterial infusion chemotherapy (HAIC) has emerged as an important strategy for unresectable hepatocellular carcinoma (uHCC), yet comparative data on efficacy and safety between different anti-angiogenic agents (lenvatinib [LenHAP] or bevacizumab [BevHAP]) remain lacking, especially in patients with potential resectable features (PotenR).MethodsThis retrospective study included patients from 3 hospitals. Included patients received LenHAP or BevHAP as the first-line treatment. The overall survival (OS), progression-free survival (PFS), objective response rate (ORR), conversion resection rate (CRR) and adverse events (AE) were compared.ResultsWe included 108 uHCC patients in each group after propensity score matching (PSM), of which PotenR patients accounted for 34.3%. Compared with BevHAP group, the LenHAP group demonstrated significantly prolonged median PFS (12.6 vs. 8.1 months; HR, 0.64; 95% CI, 0.46-0.90; p=0.0085), with a trend toward improved OS (26.4 vs. 19.6 months; HR, 0.71; 95% CI, 0.41-1.1; p=0.091). PotenR patients receiving LenHAP achieved superior outcomes, including markedly extended OS (both not reached in median, p=0.018), PFS (19.8 vs. 11.5, months, p=0.0067), and higher conversion resection rates (52.6% vs. 25.0%, p=0.015). Both regimens showed comparable safety profiles, with similar frequencies of grade 3–4 adverse events (47.2% vs. 39.8%, p=0.27) and serious adverse events (4.6% vs. 8.3%, p=0.27).ConclusionsLenHAP might offer enhanced clinical benefits over BevHAP in uHCC, particularly for PotenR patients, while maintaining equivalent tolerability.